Palliative care provision for those with non-malignant respiratory disease: a literature review. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - McVeigh, Clare; Porter, Sam; Reid, Joanne; Hudson, Peter; Larkin, Philip
Abstract : Background: It is recognised that those suffering from a malignant disease have access to excellent palliative care (PC) provision. It is less clear if the same standards of PC services are available to those with non-malignant respiratory disease (NMRD). There is therefore a need to explore the needs of people suffering from NMRD and their carers. Objectives: The purpose of this review was to determine the experience that those with NMRD have of current PC provision, and identify gaps and needs that require to be addressed. Design: A comprehensive search of the literature was undertaken, using key terms, of the following databases; CINAHL Plus, MEDLINE and the Cochrane Database of Systematic Reviews. 622 articles were sourced and inclusion and exclusion criteria were applied to highlight the most relevant literature. Results: 22 studies were reviewed using a systematic approach. Five themes emerged from the literature. (1) symptom management – greater PC support is needed. (2) palliative care provision – patients with NMRD have the same palliative care needs as those with MRD, however they do not receive the same standard of PC service provision. (3) health service provision – there is inadequate PC health service provision for those with NMRD. (4) family care givers – family care givers of NMRD sufferers have a range of unmet needs. (5) communication and information – lack of information can lead to anxiety and fear for their future. Conclusion: Palliative care is required by all those suffering from complex and persistent symptoms resulting from a non-curative illness. Those suffering from a non-malignant disease are not having their needs recognised effectively and therefore not receiving the appropriate palliative health service provision. Further research is required into the palliative healthcare provision available to those with NMRD. This research is currently being carried out by the author.